Perioperative Circulating Tumor Cells (CTCs), MCTCs, and CTC-White Blood Cells Detected by a Size-Based Platform Predict Prognosis in Renal Cell Carcinoma - Zhenlong Wang (Hindawi Limited, 2021)
To explore the clinical significance of the perioperative counts of circulating tumor cells (CTCs), mesenchymal CTCs (MCTCs), and CTC- white blood cells (WBCs) in renal cell carcinoma patients. A total of 131 patients with renal cancer who underwent operation excision from our hospital were enrolled. In addition, 20 patients with benign renal diseases were recruited as a control. Blood samples were collected from the 131 patients, before operation and 3 months after surgery. Samples were also obtained simultaneously from the control group. CanPatrol CTC detection technique was used to enrich and identify CTCs, MCTCs, and CTC-WBCs. All enrolled patients were T1-3N0M0. From these, 52 patients with renal cancer underwent radical resection, while other 79 patients underwent nephron-sparing surgery. The positive rate of CTC, MCTC, and CTC-WBC before surgery were 95.4% (125/131), 61.1% (80/131), and 11.5% (15/131), respectively. Preoperative total CTCs, MCTCs, or CTC-WBCs were poorly correlated with patients’ parameters. Preoperative CTC, MCTC, or CTC-WBC showed no association with progression-free survival (PFS). In contrast, postoperative total CTCs (≥6), positive MCTCs, and positive CTC-WBCs significantly correlated with recurrence and metastasis. These results remained independent indicators for worse PFS. In addition, the increased CTC and MCTC count after surgery also correlated with unfavorable PFS. The detection of six or more total CTCs, MCTC, or CTC-WBCs in peripheral blood after surgery might help to identify a subset of patients that have higher recurrent risk than the overall population of patients with at different stages of renal cancer.